Programas públicos de concessão de microcrédito para apoio ao microempreendedor no município de São José dos Campos/SP - Busnardo, Fábio Felippe (2014)
This paper presents public programs of microcredit financing to entrepreneurs in the three levels of government, namely, Federal, State, and Municipal, specifically in the city of São José dos Campos. The primary objective of this study is to verify how the entrepreneur may use the microcredit when you need to deploy the business to be managed, or to make some improvement that adds value to their work, and how this credit can bring increased income to the entrepreneur and function as an instrument to combat unemployment in the country as a whole. The methodology can be classified as bibliographical research, and verified by the method of multi-case studies. The context of the monograph presents, as a result of the research, the main features, benefits, ways to use and differences of public programs of microcredit at the municipal, state and federal, and what are the forms available to be these entrepreneurs have recourse and availability of access to microcredit.